ANALISIS PEMBERIAN INSENTIF KERJA BERDASARKAN FISIOLOGI KERJA DITINJAU DARI ASPEK ERGONOMI - Simanjuntak, Risma A.; Maedi, Mukhamad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
Metal found company, CV Gunung Mas is company which move in heavy indus-try field. The products are drinking water pipe, gas pippe, oil pipe, etc appropriate with the order. The heart beat measuring only form measuring of energy consumtion indirectly. The more energy consumption requirement for work activities (heacy work) the more e-nergy consumed. In work physiology, 4 Kkal/menit will be considered as consumed ener-gy maximum to do heavy physic work continually. From the result of consumed energy analysis and extra wage for employees of CV. Gunung Mas in every work activity is furnace activity consume average 4,9419 Kkal/ minutes, they get extra wage in the amount of Rp 9.500 ; process of printing activity consume average energy 4,6917 Kkal/minutes, they get extra wage in the amount of Rp 5.250; grinding activity consume average energy 4,3188 Kkal/minutes, they get extra wa-ge in the amount of Rp 2.800; drilling activity consume average energy 4,2075 Kkal/mi-nutes, they get extra wage in the amount of Rp 1.750 ; storing activity consume average energy 4,1922 Kkal/minutes, they get extra wage in the amount of Rp 1.000 ; Those activity is heavy work activity. CV Gunung Mas company had been giving axtra wage appropriate with cosumed energy (from the result analysis)